2020
DOI: 10.1021/acs.nanolett.9b05092
|View full text |Cite
|
Sign up to set email alerts
|

Global Control of Stacking-Order Phase Transition by Doping and Electric Field in Few-Layer Graphene

Abstract: The layer stacking order has profound effects on the physical properties of two-dimensional van der Waals heterostructures. For example, graphene multilayers can have distinct electronic band structures and exhibit completely different behaviors depending on the stacking order. Fascinating physical phenomena, such as correlated insulators, superconductors, and ferromagnetism, can also emerge with a periodic variation of the layer stacking order, which is known as the moiré superlattice in van der Waals materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 28 publications
7
66
0
Order By: Relevance
“…At a small twist angle, the lattice energetically prefers to relax into triangular domains with alternating domains of ABAB and ABCA as a result of the atomic reconstruction. 16,27 Figure 1c shows an amplitude image from single-frequency LPFM that is consistent with those reported by McGilly et al 19 Although single-frequency LPFM can give reliable images on flat surfaces, it can also be sensitive to artifacts, 28 many of which are associated with shifts in the contact resonance frequency induced by the change in tip-sample contact stiffness leading to common misinterpretations of single-frequency measurements. 29 Accordingly, we also imaged the sample using dual-AC-resonance-tracking (DART) mode LPFM.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…At a small twist angle, the lattice energetically prefers to relax into triangular domains with alternating domains of ABAB and ABCA as a result of the atomic reconstruction. 16,27 Figure 1c shows an amplitude image from single-frequency LPFM that is consistent with those reported by McGilly et al 19 Although single-frequency LPFM can give reliable images on flat surfaces, it can also be sensitive to artifacts, 28 many of which are associated with shifts in the contact resonance frequency induced by the change in tip-sample contact stiffness leading to common misinterpretations of single-frequency measurements. 29 Accordingly, we also imaged the sample using dual-AC-resonance-tracking (DART) mode LPFM.…”
Section: Resultssupporting
confidence: 79%
“…Both the amplitude (Figure 2b) and phase images (Figure 2c) show moiré superlattices with separated domains and domain walls, consistent with the expected atomic reconstruction. 16,27 According to previous reports, ABAB domains should have lower energy compared with the ABCA domains, leading to the bending of domain walls into ABCA domains, with the resulting concave ABCA domains. 14,27 In Figures 2b-c the dashed white curves outline the ABAB and ABCA domains where ABAB is convex while ABCA is concave.…”
Section: Resultsmentioning
confidence: 91%
“…The moiré period from fast Fourier transform (FFT; Fig. 2A, inset) is determined to At near-0° twist, the lattice energetically prefers to reconstruct into relaxed triangular domains with an alternating stacking sequence (14,38,39). In twisted trilayer graphene (tTG) and tetralayer tDBG, these domains correspond to Bernal (ABA and ABAB) and rhombohedral stacking (ABC and ABCA), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that applying molecular absorption or an external electric field can drive the stacking order transition and generate domain wall motion in graphene layers 17,22,23 . There is inevitable residue on graphene with molecular doping, which hinders the properties of graphene.…”
Section: Introductionmentioning
confidence: 99%